Morphological Changes in the Testes in Cryptorchidism in Children - o’g’li, Shukrulloyev Fayozjon Zokirjon (American Journal of Biomedicine and Pharmacy, 2024)
Cryptorchidism, the condition of undescended testes, remains one of the most common congenital anomalies in male infants, with a prevalence ranging from 1% to 8% at birth depending on the population. In many cases, the testes descend spontaneously within the first six months of life. However, about 1% of boys have testes that remain undescended and may require surgical correction (orchiopexy), ideally performed before the age of one to minimize long-term risks such as infertility and testicular cancer. Recent studies have noted variations in cryptorchidism prevalence by geographical and environmental factors.